Endoplasmic Reticulum–Mitochondria Calcium Communication and the Regulation of Mitochondrial Metabolism in Cancer: A Novel Potential Target - Bustos, Galdo; Cruz, Pablo; Lovy, Alenka; Cárdenas, César (Frontiers in Oncology, 2017)
Cancer is characterized by an uncontrolled cell proliferation rate even under low nutrient availability, which is sustained by a metabolic reprograming now recognized as a hallmark of cancer. Otto Warburg was the first to establish the relationship between cancer and mitochondria, however, he interpreted enhanced aerobic glycolysis as mitochondrial dysfunction. Today it is accepted that many cancer cell types need fully functional mitochondria to maintain their homeostasis. Calcium (Ca+2) ¬─a key regulator of several cellular processes─ has proven to be essential for mitochondrial metabolism. Inositol 1,4,5-trisphosphate receptor (IP3R)-mediated Ca2+ transfer from the endoplasmic reticulum to the mitochondria through the mitochondrial calcium uniporter (MCU) proves to be essential for the maintenance of mitochondrial function and cellular energy balance. Both, IP3R and MCU are overexpressed in several cancer cell types and the inhibition of the Ca2+ communication between these two organelles causes proliferation arrest, migration decrease and cell death through mechanisms that are not fully understood. In this review, we summarize and analyze the current findings in this area, emphasizing the critical role of Ca2+ and mitochondrial metabolism in cancer and its potential as a novel therapeutic target.